2018
DOI: 10.1525/mp.2018.36.1.98
|View full text |Cite
|
Sign up to set email alerts
|

Tendency Towards the Average? The Aesthetic Evaluation of a Quantitatively Average Music Performance

Abstract: The present study has investigated the minimal-distance hypothesis in music (Langlois & Roggman, 1990; Repp, 1997) by replicating Repp's original study (1997) on the aesthetic quality of an averaged performance—compared to individual interpretations—of Robert Schumann's Träumerei (Op. 15, No. 7). Participants (N = 205) came from Germany and Taiwan and made up a convenience sample representing different degrees of musical sophistication. We used a 2 × 4 mixed methods design that compared the country of data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Since its publication in 2014, the Gold-MSI has gained popularity in the field of music psychology and music education. For example, researchers used the Gold-MSI inventory to classify participants as musically trained or untrained (Bauer, Kreutz, & Herrmann, 2015; Farrugia, Jakubowski, Rhordi, & Stewart, 2015), to identify the possible influence of musical sophistication on research results (Kopiez, Wolf, Platz, & Mons, 2016; Wolf, Kopiez, Platz, Lin, & Mütze, 2018), and to keep track of the musical development trajectories of students in a school setting (Fiedler & Müllensiefen, 2017). Due to the applicability of the Gold-MSI inventory in various research settings, we are convinced that the adaptation of the Gold-MSI into Traditional Chinese for the Taiwanese population will make an essential contribution to the research literature and future cross-cultural research.…”
Section: Introductionmentioning
confidence: 99%
“…Since its publication in 2014, the Gold-MSI has gained popularity in the field of music psychology and music education. For example, researchers used the Gold-MSI inventory to classify participants as musically trained or untrained (Bauer, Kreutz, & Herrmann, 2015; Farrugia, Jakubowski, Rhordi, & Stewart, 2015), to identify the possible influence of musical sophistication on research results (Kopiez, Wolf, Platz, & Mons, 2016; Wolf, Kopiez, Platz, Lin, & Mütze, 2018), and to keep track of the musical development trajectories of students in a school setting (Fiedler & Müllensiefen, 2017). Due to the applicability of the Gold-MSI inventory in various research settings, we are convinced that the adaptation of the Gold-MSI into Traditional Chinese for the Taiwanese population will make an essential contribution to the research literature and future cross-cultural research.…”
Section: Introductionmentioning
confidence: 99%
“…Some categories of listeners, furthermore, tend to prefer more prototypical performances (Repp, 1997a; A. Wolf, Kopiez, Platz, Lin, & Mütze, 2018). Thus, our pianists may not have been driven to create particularly idiosyncratic interpretations.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Repp (1997b) showed that early-career musicians tend to play more prototypically than do established musicians. Some categories of listeners, furthermore, tend to prefer more prototypical performances (Repp, 1997a;A. Wolf, Kopiez, Platz, Lin, & Mu ¨tze, 2018).…”
Section: Quantity Of Motionmentioning
confidence: 99%
“…The performance parameters on which these assessments are based are not only subjective but also ill-defined, leading to large differences in subjective opinion among music educators (Thompson and Williamon, 2003;Wesolowski et al, 2016). However, other studies have shown that humans tend to rate prototypical (average) performances higher than individual performances (Repp, 1997a;Wolf et al, 2018). This might indicate that performances are rated based on some form of perceived distance from an 'ideal' per-formance.…”
Section: Performance Assessmentmentioning
confidence: 94%